Perbandingan Akurasi Foto Toraks dan Ultrasonografi Dada dalam Diagnosis Efusi Pleura: Suatu Kajian Literatur - Salsa Nabila Inong Ramadhana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pleural effusion is the accumulation of fluid in the pleural cavity, which is a common clinical condition requiring rapid and accurate diagnosis. Imaging modalities such as chest X-ray and ultrasound (USG) of the chest play a crucial role in identifying and evaluating this condition. Chest X-ray remains the most widely used initial screening tool due to its availability and ease of use. However, chest USG offers higher sensitivity, especially in detecting small effusions, assessing fluid characteristics, and guiding diagnostic and therapeutic procedures. Additionally, USG provides real-time imaging, enhancing the safety and effectiveness of interventions such as aspiration or drainage. Although both modalities are important, USG provides more detailed information, particularly in evaluating more complex pleural fluid conditions. This review discusses the latest evidence regarding the sensitivity, specificity, advantages, and limitations of both imaging techniques. Understanding the complementary roles of chest X-ray and USG is essential for optimizing diagnostic strategies, ultimately improving clinical outcomes and enabling more effective management of pleural effusion.